Mutual relationships of biochar and soil pH, CEC, and exchangeable base cations in a model laboratory experiment - Hailegnaw, Niguss Solomon; Mercl, Filip; Pračke, Kateřina; Száková, Jiřina; Tlustoš, Pavel (Journal of soils and sediments, 2019)
Purpose The majority of biochar studies use soils with only a narrow range of properties making generalizations about the effects of biochar on soils difficult. In this study, we aimed to identify soil properties that determine the performance of biochar produced at high temperature (700 °C) on soil pH, cation exchange capacity (CEC), and exchangeable base cation (Ca 2+ , K + , and Mg 2+ ) content across a wide range of soil physicochemical properties. Materials and methods Ten distinct soils with varying physicochemical properties were incubated for 12 weeks with four rates of biochar application (0.5, 2, 4, and 8% w / w ). Soil pH, CEC, and exchangeable base cations (Ca 2+ , K + , and Mg 2+ ) were determined on the 7th and 84th day of incubation. Results and discussion Our results indicate that the highest biochar application rate (8%) was more effective at altering soil properties than lower biochar rates. Application of 8% biochar increased pH significantly in all incubated soils, with the increment ranging up to 1.17 pH unit. Biochar induced both an increment and a decline in soil CEC ranging up to 35.4 and 7.9%, respectively, at a biochar application rate of 8%. Similarly, biochar induced increments in exchangeable Ca 2+ up to 38.6% and declines up to 11.4%, at an 8% biochar application rate. The increment in CEC and exchangeable Ca 2+ content was found in soils with lower starting exchangeable Ca 2+ contents than the biochar added, while decreases were observed in soils with higher exchangeable Ca 2+ contents than the biochar. The original pH, CEC, exchangeable Ca 2+ , and texture of the soils represented the most crucial factors for determining the amount of change in soil pH, CEC, and exchangeable Ca 2+ content. Conclusions Our findings clearly demonstrate that application of a uniform biochar to a range of soils under equivalent environmental conditions induced two contradicting effects on soil properties including soil CEC and exchangeable Ca 2+ content. Therefore, knowledge of both biochar and soil properties will substantially improve prediction of biochar application efficiency to improve soil properties. Among important soil properties, soil exchangeable Ca 2+ content is the primary factor controlling the direction of biochar-induced change in soil CEC and exchangeable Ca 2+ content. Generally, biochar can induce changes in soil pH, CEC, and exchangeable Ca 2+ , K + , and Mg 2+ with the effectiveness and magnitude of change closely related to the soil’s original properties.